Implementation of Child Marriage Policy in Palu City - Muhammad Reski Febriansyah; Fentiny Nugroho (Interdisciplinary Social Studies, 2025)
This study describes and analyzes the implementation of policies for preventing and handling child marriage in Palu City, specifically regulated in Mayor Regulation Number 34 of 2023. It also identifies supporting and inhibiting factors. The policy aims to improve the Quality of Families, especially in the Quality of Legal Structures dimension, given that Central Sulawesi Province’s Family Quality Index score is 71.80, categorized as only "quite responsive" to gender and children’s rights. The research, using a descriptive qualitative approach, was conducted at the Women’s Empowerment and Child Protection Office (DP3A), the Office of Religious Affairs, and the Palu City Religious Court. The analysis follows Edward III’s model with four variables: communication, resources, disposition, and bureaucratic structure. Findings show the policy’s implementation is suboptimal. Communication suffers from ambiguous legal criteria, dual institutional authority, and poor socialization to the broader community. Resource limitations include insufficient quality and number of implementers, inadequate facilities and data, and no dedicated budget. Disposition is affected by conflicting cultural values, with communities prioritizing marriage to avoid shame over legal minimum age limits. The bureaucratic structure reveals that policies in the form of mayoral regulations without legislative backing result in low budget prioritization. Supporting factors include strong legal legitimacy and NGO backing. Main inhibiting factors are the lack of an integrated Standard Operating Procedure (POS) across sectors and regulatory gaps in managing marriage dispensation in Religious Courts.